Increased gene delivery efficiency and specificity of a lipid-based nanosystem incorporating a glycolipid - Magalhães, Mariana (2014)
Hepatocellular carcinoma (HCC) is the third most common cause of death related to cancer diseases worldwide. The current treatment options have many limitations and reduced success rates. In this regard, advances in gene therapy have shown promising results in novel therapeutic strategies. However, the success of gene therapy depends on the efficient and specific delivery of genetic material into target cells. In this regard, the main goal of this work was to develop a new lipid-based nanosystem formulation containing the lipid lactosyl-PE for specific and efficient gene delivery into HCC cells. The obtained results showed that incorporation of 15% of lactosyl-PE into liposomes induces a strong potentiation of lipoplex biological activity in HepG2 cells, not only in terms of transgene expression levels but also in terms of percentage of transfected cells. In the presence of galactose, which competes with lactosyl-PE for the binding to the asialoglycoprotein receptor (ASGP-R), a significant reduction in biological activity was observed, showing that the potentiation of transfection induced by the presence of lactosyl-PE could be due to its specific interaction with ASGP-R, which is overexpressed in HCC. In addition, it was found that the incorporation of lactosyl-PE in the nanosystems promotes an increase in their cell binding and uptake. Regarding the physicochemical properties of lipoplexes, the presence of lactosyl-PE resulted in a significant increase in DNA protection and in a substantial decrease in their mean diameter and zeta potential, conferring them suitable characteristics for in vivo application. Overall, the results obtained in this study suggest that the potentiation of the biological activity induced by the presence of lactosyl-PE is due to its specific binding to the ASGP-R, showing that this novel formulation could constitute a new gene delivery nanosystem for application in therapeutic strategies in HCC.